2017
DOI: 10.1007/s41062-017-0081-8
|View full text |Cite
|
Sign up to set email alerts
|

Seismic isolation of buildings using devices based on sliding between surfaces with variable friction coefficient

Abstract: Base isolators are effective tools that favor a high level of building performance under lateral load, providing protection to both structural and non-structural elements. In this context, this paper discusses the possibility of employing materials with different frictional properties to enhance the response of flat-and curvedsurface base isolators. Two innovative devices, referred to as ''BowTie'' and ''BowC'', are introduced and discussed in some detail. A series of non-linear time history analyses is then c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Base isolation (Chen and Li,2020) is one common strategy for minimizing seismic damage to structures. Friction pendulum system is a kind of device widely used in practice, which has outstanding load-bearing capacity and self-resetting performance (Calvi et al, 2017; Chen et al, 2022a; Chen and Jia,2021; Zayas et al, 1990; Imran et al, 2021; Madhekar and Jangid, 2010; Morgan and Mahin, 2010; Nazarnezhad and Naderpour, 2021; Shang et al, 2022; Shrimali and Jangid, 2003). Morgan and Mahin, 2010 suggested that the new multi-stage friction pendulum isolation bearing was feasible in reducing the performance goals of isolator displacement and floor acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…Base isolation (Chen and Li,2020) is one common strategy for minimizing seismic damage to structures. Friction pendulum system is a kind of device widely used in practice, which has outstanding load-bearing capacity and self-resetting performance (Calvi et al, 2017; Chen et al, 2022a; Chen and Jia,2021; Zayas et al, 1990; Imran et al, 2021; Madhekar and Jangid, 2010; Morgan and Mahin, 2010; Nazarnezhad and Naderpour, 2021; Shang et al, 2022; Shrimali and Jangid, 2003). Morgan and Mahin, 2010 suggested that the new multi-stage friction pendulum isolation bearing was feasible in reducing the performance goals of isolator displacement and floor acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…FPS has become a well-known practical IS due to its technical advantages. There are, however, some limitations with FPS and its variants [33,34]. SMA-based recentering is a relatively modern alternative solution for the restoring problem of sliding ISs [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%